A cautionary note on fecal sampling and molecular epidemiology in predatory wild great apes. Issue 8 (1st June 2015) - De Nys, Hélène Marie; Madinda, Nadège Freda; Merkel, Kevin; Robbins, Martha; Boesch, Christophe; Leendertz, Fabian Hubertus; Calvignac‐Spencer, Sébastien
<x xml:space="preserve">Abstract</x> Fecal samples are an important source of information on parasites (viruses, prokaryotes, or eukaryotes) infecting wild great apes. Molecular analysis of fecal samples has already been used for deciphering the origins of major human pathogens such as HIV‐1 or Plasmodium falciparum. However, for apes that hunt (chimpanzees and bonobos), detection of parasite nucleic acids may reflect either true infection of the host of interest or ingestion of an infected prey, for example, another non‐human primate. To determine the potential magnitude of this issue, we estimated the prevalence of prey DNA in fecal samples obtained from two wild chimpanzee communities. We observed values >15%, which are higher than or close to the fecal detection rates of many great ape parasites. Contamination of fecal samples with parasite DNA from dietary origin may therefore occasionally impact non‐invasive epidemiological studies. This problem can be addressed (at least partially) by monitoring the presence of prey DNA. Am. J. Primatol. 77:833–840, 2015. © 2015 Wiley Periodicals, Inc.